Sistem Pendeteksi Kesegaran Susu Formula Bayi Berbasis Internet Of Things - Amaliah, Asma; Nabila, Auliya (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2023)
This research was conducted to design a tool for detecting the suitability of baby formula milk based on the internet of things. This tool is designed to obtain valid data on the period of time when baby formula milk is still suitable for consumption or is no longer suitable for consumption. As is known, the duration of milk spoilage cannot be measured with certainty. There are several sensors used in this system, namely a pH sensor and a gas sensor as well as reading detection results using an LCD and sending them in real time to Telegram. The microcontroller used is ESP32. Based on data obtained from testing using a pH sensor and a gas sensor, the results obtained were that the pH sensor detected that the brewed baby formula milk was considered unfit for consumption after 4 hours in free air conditions due to the results of the pH sensor showing, namely 6.44, which is the value indicates the milk has become acidic. Meanwhile, for the gas sensor, there was a significant change in value from the initial value after 5 hours of the milk being left in free air. The pH sensor was a fairly good detection tool in detecting spoilage of baby formula milk because the MAPE obtained was 1.34%.